Using unmanned aerial vehicles to quantify spatial patterns of Nitraria tangutorum and Reaumuria songarica shrubs under different sand burial conditions in the Jiayuguan national wetland, northwest China. Issue 1 (2nd January 2020) - Zhao, Lianchun; Wang, Jiwei; Zhao, Chengzhang; Sun, Yi; Jun, Wen
ABSTRACT: sand burial is an important environmental stress affecting the distribution of plants in desert areas. It can change the spatial patterns of the population by affecting the environmental conditions. Nitraria tangutorum and Reaumuria songarica are dominant species in desert regions, and it is important to study their spatial patterns under different sand burial conditions to clarify the adaptive strategies of xerophytes. Unmanned aerial vehicles are ideal tools for the measurement of ecological phenomena. We here used an unmanned aerial vehicle to study the spatial patterns of the two species. Results show that (1) unmanned aerial vehicles can provide high-resolution (≤0.1 m) data and allow more efficient measurements than conventional ground-based survey methods; (2) with an increase in sand burial depth, the distribution of N. tangutorum showed aggregation, whereas R. songarica transformed from a clumped distribution at certain scales to a random distribution at all scales; and (3) the interspecific relationship between the two species changed from uncorrelated at all scales to correlated at a small scale. Our results suggest that the adaptability of N. tangutorum to a sandy environment is stronger than that of R. songarica . This may reflect the adaptive mechanism of xerophytes in desert areas.